Hubungan Tingkat Pengetahuan Pasien Hipertensi dengan Kepatuhan Minum Obat pada Lansia di Poliklinik Rumah Sakit Islam Sultan Agung Banjarbaru - Rahmadi; Herry Susanto; Kurnia Wijayanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension is a non-communicable disease that significantly contributes to morbidity and mortality, particularly among the elderly. Patient knowledge about hypertension plays a crucial role in determining their adherence to medication, especially in taking antihypertensive drugs regularly. This study aims to analyze the relationship between the level of hypertension knowledge and medication adherence in elderly patients at the Sultan Agung Islamic Hospital Banjarbaru Polyclinic. This study used a quantitative correlational approach with a cross-sectional design. A sample of 35 respondents was obtained using accidental sampling technique. Data were collected using standardized questionnaires to measure knowledge (correct/incorrect scores) and adherence (using the modified MMAS-8 score 0–8). Data analysis included descriptive statistics, chi-square test, and Odds Ratio (OR) calculation at α = 0.05. The results showed a significant relationship between the level of knowledge and medication adherence (p = 0.002). The OR value of 17.33 (95% CI: 2.17–138.18) indicates that elderly patients with low knowledge have a much higher chance of non-adherence to medication compared to those with good knowledge. Based on these findings, it is recommended to develop targeted educational programs for the elderly focusing on increasing knowledge about hypertension and the importance of medication adherence, along with involving families to support medication adherence in hypertensive patients. This educational program could help improve the quality of life for the elderly by better managing hypertension.